Anelastic relaxation processes due oxygen in Nb-3.1 at.% Ti alloys - Almeida, L. H.; Niemeyer, T. C.; Pires, KCC; Grandini, Carlos Roberto [UNESP]; Pintao, CAF; Florencio, O. (Elsevier B.V., 2004)
In the last 50 years several studies have been made to understand the relaxation mechanisms of the heavy interstitial atoms present in transition metals and their alloys. Internal friction measurements have been carried out in a Nb-Ti alloy containing 3.1 at.% of Ti produced by the Materials Department of Chemical Engineering Faculty of Lorena (Brazil), with several quantities of oxygen in solid solution using a torsion pendulum. These measurements have been performed by a torsion pendulum in the temperature range from 300 to 700 K with an oscillation frequency between 0.5 and 10 Hz. The experimental results show complex internal friction spectra that have been resolved, into a series of Debye peaks corresponding to different interactions. For each relaxation process it was possible to obtain the height and temperature of the peak, the activation energy and the relaxation time of the process. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: anelasticity; internal friction; Nb-Ti alloys; interstitials